Menopausal Symptoms Among Post-Menopausal Women in Selected Wards of Lalitpur Metropolitan City - Lawot, Isabel; Bajracharya, Karuna; Singh, Shreejana; Joshi, Deepak Raj (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Menopause is permanent cessation of menstruation for more than a year resulting from the loss of follicular activity of the ovaries. In Nepal, menopause is considered as a normal phenomenon and thus women themselves may not seek medical help and not understand the complications and issues associated with menopause. Therefore, this study aims to assess menopausal symptoms among post-menopausal women. Methods: A descriptive cross-sectional research design was used to assess menopausal symptoms among postmenopausal women of age group 45-60 years residing in Lalitpur Metropolitan city, Nepal. One stage cluster sampling was used to select 273 respondents. Descriptive and inferential statistical methods were used to analyze data. Results: Out of 273 postmenopausal women, mean age was 53.4 ± 3.8years. The most common symptoms were physical and mental exhaustion 221 (81 %) followed by joint and muscular discomfort 213 (78 %), hot flushes and sweating 203 (74.4%). Among somato-vegetative symptoms, the severity of hot flushes and sweating was reported by 124 women (43.4%). Regarding psychological symptoms, the severity of physical and mental exhaustion wasreported by 92 women (33.7%). For urogenital problems, the severity of sexual issues was reported by 78 women (28.6%). Conclusions: It is concluded that more than half of the participants experienced mild to very severe menopausal symptoms especially hot flushes, sweating, joint and muscular discomfort, physical and mental exhaustion, sexual problems etc. These symptoms are significantly associated with physical activities and alcohol consumption.